2014
DOI: 10.2217/cpr.14.5
|View full text |Cite
|
Sign up to set email alerts
|

Food-related parenting practices and child and adolescent weight and weight-related behaviors

Abstract: Summary The prevalence of overweight and obesity in children has reached a concerning plateau in the past three decades, with overweight or obesity impacting approximately one-third of youth. Unhealthy weight-related behaviors, including dieting, unhealthy weight control practices and binge eating, are also a great public health concern for young people given both their high prevalence and harmful consequences. Food-related parenting practices, including food restriction and pressure-to-eat, have been associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 93 publications
(103 reference statements)
3
32
0
2
Order By: Relevance
“…1316,6369 Further, the present study demonstrated no cross-sectional associations with food restriction or pressure-to-eat and better dietary intake outcomes. Thus, while parents likely adopt directive forms of control with the goal of improving their child’s dietary intake or weight status, findings from the present study, in combination with previous studies exploring the impact of food restriction and pressure-to-eat on child outcomes, 9,10 suggest these forms of control might yield unintended results.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…1316,6369 Further, the present study demonstrated no cross-sectional associations with food restriction or pressure-to-eat and better dietary intake outcomes. Thus, while parents likely adopt directive forms of control with the goal of improving their child’s dietary intake or weight status, findings from the present study, in combination with previous studies exploring the impact of food restriction and pressure-to-eat on child outcomes, 9,10 suggest these forms of control might yield unintended results.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, although our sample was not particularly large, it was adequate for the analyses conducted and allowed for examination of associations within an under-explored age group. Previous work exploring food-related parenting practices has been conducted primarily in samples of toddlers, preschoolers, and early-elementary school aged children, 3538,40,48 with some more recent work exploring the impact of these practices on adolescents; 10,20,25,74,75 thus we were able to fill a gap in the literature by examining associations within a population of late-elementary school children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, disordered eating behaviours have been found to associated with a number of undesirable outcomes including increased risk of eating disorders and obesity, in adolescents. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of behavioural factors within the family context has been explored. This is especially true for food-related behaviours [11][12][13] , but also physical activity, sleep, media consumption 14,15 , and, albeit much rarer, psychosocial factors like e.g. lack of social networks have been shown to be associated with childhood obesity 16 .…”
Section: Introductionmentioning
confidence: 99%